2006
DOI: 10.1128/mcb.26.8.2947-2954.2006
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Targeting of p33ING1b by Phosphorylation-Dependent 14-3-3 Binding Regulates p21WAF1 Expression

Abstract: ING1 is a type II tumor suppressor that affects cell growth, stress signaling, apoptosis, and DNA repair by altering chromatin structure and regulating transcription. Decreased ING1 expression is seen in several human cancers, and mislocalization has been noted in diverse types of cancer cells. Aberrant targeting may, therefore, functionally inactivate ING1. Bioinformatics analysis identified a sequence between the nuclear localization sequence and plant homeodomain domains of ING1 that closely matched the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…As the potential PDSMs of ING2 and p33ING1b are sumoylated or phosphorylated, respectively, this strongly suggests that ING2 sumoylation could be regulated by an adjacent phosphorylation site and, reciprocally, that ING1 phosphorylation could regulate its potential sumoylation. Gong et al (2006) observed p33ING1b exportation from the nucleus after 14-3-3Z overexpression. Thus, even if under our experimental conditions we observed that ING2 subcellular localization is independent on its sumoylation, we cannot exclude that in other conditions sumoylation of ING2 could be involved in this process.…”
Section: Ing2 Sumoylation and Sin3a Mediate Gene Expressionmentioning
confidence: 83%
See 1 more Smart Citation
“…As the potential PDSMs of ING2 and p33ING1b are sumoylated or phosphorylated, respectively, this strongly suggests that ING2 sumoylation could be regulated by an adjacent phosphorylation site and, reciprocally, that ING1 phosphorylation could regulate its potential sumoylation. Gong et al (2006) observed p33ING1b exportation from the nucleus after 14-3-3Z overexpression. Thus, even if under our experimental conditions we observed that ING2 subcellular localization is independent on its sumoylation, we cannot exclude that in other conditions sumoylation of ING2 could be involved in this process.…”
Section: Ing2 Sumoylation and Sin3a Mediate Gene Expressionmentioning
confidence: 83%
“…p33ING1b has been reported to be phosphorylated on serine 199 (S199) to regulate its amount in the nucleus. Indeed, this phosphorylation event was shown to be required for p33ING1 binding to the 14-3-3Z cargo protein in order to be exported from the nucleus (Gong et al, 2006). Interestingly, the serine 199 of ING1 is the serine residue belonging to the potential PDSM.…”
Section: Ing2 Sumoylation and Sin3a Mediate Gene Expressionmentioning
confidence: 99%
“…In this study, we found that rapid ING3 degradation has an important role in the loss of ING3 expression in advanced melanomas, thereby providing another explanation of aberrant ING3 expression in melanomas in addition to our previous finding that subcellular relocalization of ING3 causes its deregulation in both primary and metastatic melanomas (Wang et al, 2007). Meanwhile, ING1b has been shown to be shifted from the nucleus to the cytoplasm in melanocytic lesions (Nouman et al, 2002), which may be mediated by 14-3-3 proteins (Gong et al, 2006). Both nuclear ING2 and overall ING4 expressions are also downregulated in melanomas, although only the reduced ING4 expression was significantly associated with melanoma progression (Lu et al, 2006;Li et al, 2008).…”
Section: Discussionmentioning
confidence: 66%
“…Studies revealed that 14-3-3 family members primarily reside in the cytoplasm and are associated with phosphorylated ligands involved in numerous cellular processes, including regulation of the cell cycle and DNA damage checkpoints. Binding to 14-3-3 causes tethering of significant amounts of p33 ING1b in the cytoplasm (33,34). Moreover, other studies have demonstrated that cytoplasmic p33…”
Section: Ing1bmentioning
confidence: 98%
“…ING1b particularly binds to members of the 14-3-3 family through phosphorylation at serine residue 199 (33). Studies revealed that 14-3-3 family members primarily reside in the cytoplasm and are associated with phosphorylated ligands involved in numerous cellular processes, including regulation of the cell cycle and DNA damage checkpoints.…”
Section: Ing1bmentioning
confidence: 99%